TAMBORA SEBUAH PERJALANAN VISUAL - Kurnia S F, Aka; Syukron Anshori, Muhammad (Jurnal TAMBORA, 2020)
The purpose of this research is to reflect back 200 years of the eruption of Tambora on the island of Sumbawa, West Nusa Tenggara through travel with a photographic study approach, specifically travel photography. Since its inception, photography has played a constitutive role in shaping a travel record, this is also comparable to the importance of that role as a depiction of social identity (Osborne, 2000). In addition, travel photography is also a way to see experiences through visual authentication (Hilman Wendy, 2007). Mount Tambora erupted in April 1815, impacting global climate change and natural disasters which claimed 84,000 lives on the island of Sumbawa, and buried the Tambora kingdom and Concentrated .. Based on the results of research, researchers see the occurrence of reconstruction in the history of the eruption of Tambora which is not only seen as a mountain, but also as an identity in the social structure of society in the form of photography. A photographer has the authority to create a reality from pre-travel to post-travel.